2000
DOI: 10.3168/jds.s0022-0302(00)75096-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inbreeding on Production and Survival in Jerseys

Abstract: Responses of registered Jersey cows to various levels of inbreeding were examined with pedigree data supplied by the American Jersey Cattle Association and test-day production data from 1970 through 1998 obtained from the Animal Breeding Center at Cornell University. Rate of increase in level of inbreeding is accelerating with time, making it more difficult for producers to make matings that avoid the potentially deleterious effects of inbreeding. Production losses caused by inbreeding were significant and cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 18 publications
4
27
0
4
Order By: Relevance
“…A decreased survival rate of Jerseys has been observed as the level of inbreeding increased. Survival is likely to have a greater negative impact on the financial health of the dairy enterprise than production losses (Thompson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A decreased survival rate of Jerseys has been observed as the level of inbreeding increased. Survival is likely to have a greater negative impact on the financial health of the dairy enterprise than production losses (Thompson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly it can be supposed that the mean inbreeding as well as the mean relationship of them are much higher than indicated by means of only three generations of ancestors. To what extent inbreeding results in depression and threatens a population, is the topic of investigations mostly concerning foreign cattle populations (THOMPSON et al 2000a, b, BIFFANI et al 2002, CARAVIELLO et al 2003, CASSEL et al 2003a, b, UZMAY and AKBAS 2003. It was shown that inbreeding causes depression in all traits which are important for dairy breeding, such as constitution, fertility, and duration of use, which are the traits characterized by a low heritability.…”
Section: Inbreeding and Main Contributorsmentioning
confidence: 99%
“…Este resultado, es distinto de lo que menciona Thompson et al (2000), quienes reportan que altos índices de endogamia producen un deterioro marcado del rendimiento productivo, de alrededor de 0,5 y 1,5 kg menos de leche por día.…”
Section: Ettema Y Santos 2004)unclassified